2021
DOI: 10.36253/wep-9893
|View full text |Cite
|
Sign up to set email alerts
|

Motivation factors for organic wines. An analysis from the perspective of German producers and retailers

Abstract: This study investigates the motives for producers that inform decisions to convert or not convert to organic wine production as well as the motives for retailers to offer or not offer organic wine and promotion of organic wine from producers’ and retailers’ perspectives. In total, 100 semi-structured in-depth interviews with 25 different types of retailers, 50 organic wineries and 25 non-organic wineries were conducted and analysed using content analysis and grounded theory. Additionally, the wine offers of 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…In addition, this study may contribute positively to the debate on the relationship between the preferences of wine cooperative consumers and their organic choices. The results describe how familiar consumers are with organic and cooperative-produced wines, pointing out the opportunity for wines produced by cooperatives to better target the market segments that mainly choose organic products [74].…”
Section: Discussionmentioning
confidence: 93%
“…In addition, this study may contribute positively to the debate on the relationship between the preferences of wine cooperative consumers and their organic choices. The results describe how familiar consumers are with organic and cooperative-produced wines, pointing out the opportunity for wines produced by cooperatives to better target the market segments that mainly choose organic products [74].…”
Section: Discussionmentioning
confidence: 93%
“…The main reasons to produce organic wine have been addressed, at least to some degree, by the literature on sustainability (Castellini et al., 2014; Cobelli et al., 2021; Dodds et al., 2013; Fairweather, 1999; Hauck et al., 2021). Researchers have relied mostly on the resource-based view (RBV) to explain organic production as a winery's decision to ensure the continuous availability of resources, sustained profits and growth (García-Cortijo et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Germany, [26] found that 40% of consumers are unaware that organic wine exists. Later, [3] found that wineries often did not communicate the production of organic wine. The reason for producing organic wines is related more to their own values and attitudes than to promotional outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As part of the European agricultural sector, German wine producers are expected to increase the share of organically cultivated vineyards to 25% by 2030 [2]. While the share of organic vineyards has risen strongly over the past decades, the demand for organically produced wines could not keep up with the growth in supply [3]. There are consumer groups that show a higher interest in organic wines, such as highly involved wine drinkers.…”
Section: Introductionmentioning
confidence: 99%